Independent Curriculum as an Effort to Improve the Quality of Learning for Students After the Covid-19 Pandemic (Universitas Pamulang, 2025)
In the face of changes due to the pandemic, of course, teaching and learning activities give rise to various problems, one of which is the lack of motivation to learn so that it affects the quality of learning that is far from the maximum and has an impact on decreasing student learning achievements. The writing of this article aims to analyze the independent curriculum in an effort to improve the quality of student learning after the Covid-19 pandemic. The writing of this article uses a literature study method derived from journals, books, websites, and other supporting literature documents. The results of this study show that the independent curriculum can help improve the quality of post-pandemic learning with interactive and relevant and competency-based learning. The role of the independent curriculum in helping to recover and improve the quality of learning that has declined due to the pandemic is quite good, but there needs to be further research, namely whether the independent curriculum is able to